NAT444 solution to the dial-up address occupation in NFV environment - Yongming YAN; Bin XU; Haifeng XU; Kechuang YE (Dianxin kexue)
With the boom of NFV technology,the traditional network hardware was being replaced.For telecom operators,NFV was expected to deploy on the universal server,which could reduce the CAPEX and OPEX,improve operational efficiency,achieve rapid deployment of new service,and ultimately increase the operator's revenue.However,NFV had its unique characteristics,which would consume a large amount of public IPv4 addresses if we used the same deployment and configuration as traditional network hardware in the scenarios of enterprise PPPoE dial-up network.NAT444 was introduced in NFV environment as a solution,including the deployment and traceability system.